Tanggung Jawab Hukum Pengelolaan Dana Bantuan Operasional Sekolah Di SD Negeri 1 Kunjeng Kecamatan Gubug Kabupaten Grobogan - Marshanda Salsadella; Edi Pranoto (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Schools, as educational facilities, have a crucial role in improving the quality and standards of national education to make it more advanced. In line with the introduction to PERMENDIKBUD No. 18 of 2019, the government provides compensation in the form of School Operational Assistance Funds (BOS) with the aim of helping fund school operational and non-personnel costs. Implementing school operational assistance is part of the state's responsibility to provide financing to the entire community and is an implementation of the mandate of the 1945 Constitution of the Republic of Indonesia to make the nation's life intelligent. Therefore, the author is interested in analyzing it in research entitled "Legal Responsibilities for Management of School Operational Assistance Funds at SD Negeri 1 Kunjeng, Gubug District" with the problem of what is the legal basis for managing School Operational Assistance Funds (BOS) at SD Negeri 1 Kunjeng and how? Legal responsibility for managing social assistance funds at SD N 1 Kunjeng, Gubug District. This research uses normative juridical which focuses on secondary data supported by the results of interviews and observations and analyzed qualitatively. Based on the research results, it can be concluded that the legal basis for managing BOS funds at SD Negeri 1 Kunjeng is rooted in the 1945 Constitution, specifically Article 31B paragraphs (2) and (3), which requires the state to organize an equitable and high-quality national education system. UUSPN No. 20 of 2003 also becomes the legal basis with Article 50 paragraph (2) which requires the government to provide financial assistance for basic education. Technical instructions from PERMENDIKBUD No. 2 of 2022 provides detailed regulations regarding the management of BOS funds according to the needs of educational units, supporting the government's efforts to create equal and quality access to education. Legal responsibility for managing BOS funds at SD Negeri 1 Kunjeng is centered on the principal and the entire school. The 1945 Constitution requires the state to provide free basic education through a 9-year compulsory education program. BOS funds, as a state financial tool, are channeled directly to schools with the principles of flexibility and transparency